Phthalate Syndrome: From Disrupted Fetal Steroidogenesis to Neurobehavioural Demasculinisation. A Narrative Review - Psiuk, Arkadiusz Adam; Szymocha, Joanna; Tsukerman, Jarosław; Wojas, Aleksandra; Pardela, Rafał; Palian, Jakub; Huzarska, Karolina; Baraniecka, Aleksandra; Kurzyński, Szymon; Smędowski, Igor (Quality in Sport, 2026)
Background: Phthalates are diesters of phthalic acid used widely as plasticisers in plastics, food-contact materials, medical devices and personal-care products. As non-persistent endocrine-disrupting chemicals (EDCs), they may interfere with fetal androgen biosynthesis during the masculinisation programming window (MPW; 8–14 weeks' gestation) and have been associated with disorders collectively termed "phthalate syndrome". Aim: To synthesise current evidence on the proposed pathomechanistic axis linking maternal phthalate exposure with disrupted fetal steroidogenesis, the phenotype of testicular dysgenesis syndrome (TDS) and longer-term neurobehavioural and andrological consequences. Material and methods: PubMed/MEDLINE, Scopus, Web of Science and Embase were searched for original studies, reviews, meta-analyses and biomonitoring reports published 2000–2025, using "phthalates", "endocrine-disrupting chemicals", "Leydig cell", "INSL3", "anogenital distance", "testicular dysgenesis", "masculinisation programming window", "neurodevelopment", "autism" and "ADHD". Results: Reviewed evidence indicates that maternal monoester metabolites cross the placenta and may suppress steroidogenic transcripts (StAR, TSPO, CYP11A1, CYP17A1, 3β-HSD) and INSL3 in fetal Leydig cells. Several cohorts associate higher prenatal biomarkers with shortened anogenital distance and, less consistently, with cryptorchidism and hypospadias. Higher in utero exposure has further been linked with diminished male-typed play, autistic traits, ADHD symptomatology and compensated Leydig cell failure in adulthood. Conclusions: Prenatal phthalate exposure plausibly perturbs androgenic programming along a continuum extending from the gonad to the developing brain. Preventive public-health and preconceptional risk-reduction measures appear warranted.